Q. 195.0( 1 Vote )

Mark the correct

Answer :

Given that function f : R R where f(x) = (x – 1) (x – 2) (x – 3)


If f(x) = f(y)


Then


(x – 1) (x – 2) (x – 3) = (y – 1) (y – 2) (y – 3)


f(1) = f(2) = f(3) = 0


So, f is not one-one.


y = f(x)


x ϵ R also y ϵ R so f is onto.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

| Let * be a binaMathematics - Board Papers

Find the idMathematics - Board Papers

Let f : A Mathematics - Exemplar

Show that the binMathematics - Board Papers

Determine whetherRD Sharma - Volume 1

Fill in theMathematics - Exemplar